Édouard Glissant, Philosopher : Heraclitus and Hegel in the Whole-World. - Leupin, Alexandre, 1948- (SUNY series in contemporary French thought., 2021)
One of the greatest writers of the late twentieth century, Édouard Glissant's body of work covers multiple genres and addresses many cogent contemporary problems, such as borders, multiculturalism, postcolonial and decolonial studies, and global humanities. Édouard Glissant, Philosopher is the first study that maps out this writer's entire work in relation to philosophy. Glissant is reputed to be a "difficult writer;" however, Alexandre Leupin demonstrates the clarity and coherence of his thinking. Glissant's rereading of Western philosophy entirely remaps its age-old questions and offers answers that have never been proposed. In doing so, Glissant offers a new way to think about questions that are at the forefront of Global Humanities today: identity, race, communities, diasporas, slavery, nation-states and nationalism, aesthetics, ethics, and the place and function of poetry and art in a globalized world. This book will elucidate Glissant's theoretical writings, not only in England and in America but also in the anglophone Caribbean, Africa, and India.